2000
DOI: 10.1111/j.1651-2227.2000.tb00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oral hypo‐osmolar glucose‐based and rice‐based oral rehydration solutions in the treatment of cholera in children

Abstract: Patients who received rice-based hypo-osmolar ORS had subsequently reduced (p < 0.05) stool output, ORS consumption and diarrhoea duration than the patients who received either WHO-ORS or glucose-based hypo-osmolar ORS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…In other studies, ORS was shown to decrease the duration of diarrhea and rate of purging. Not surprisingly, rice-based hypoosmolar ORS was better than standard ORS or RO-ORS in cholera patients (25). Rice has the advantage of providing glucose, amino acids, and more calories than an equivalent amount of glucose and is hypoosmolar to standard WHO-ORS.…”
Section: Rice-based Orsmentioning
confidence: 93%
“…In other studies, ORS was shown to decrease the duration of diarrhea and rate of purging. Not surprisingly, rice-based hypoosmolar ORS was better than standard ORS or RO-ORS in cholera patients (25). Rice has the advantage of providing glucose, amino acids, and more calories than an equivalent amount of glucose and is hypoosmolar to standard WHO-ORS.…”
Section: Rice-based Orsmentioning
confidence: 93%
“…Thus, it is difficult to find only one explanation for the beneficial effect of Rice-ORS: one explanation would be that rice increased the local colonic concentration of SCFA, which in turn stimulated water absorption and reduced stool output (Argenzio and Whipp, 1979;Roediger and Moore, 1981;Binder and Mehta, 1989;Ramakrishna and Roediger, 1990). Alternatively, stool output may have been reduced by another mechanism as suggested in previous studies (Macleod et al, 1995;Mathews et al, 1999;Dutta et al, 2000;Murphy et al, 2004;Gregorio et al, 2009), which in turn may have increased the SCFA concentration in the stools.…”
Section: Faecal Scfas and Microbiota In Children S Monira Et Almentioning
confidence: 94%
“…Initially, glucose was the first carbohydrate to be used (Desjeux et al, 1994). Then, rice (Molla et al, 1982;Gore et al, 1992;Desjeux et al, 1994;Dutta et al, 2000) and more recently amylase-resistant starch (ARS) (Ramakrishna et al, 2000Raghupathy et al, 2006) added to glucose ORS has proven to be more effective than glucose ORS without ARS.…”
Section: Introductionmentioning
confidence: 99%
“…Rice-based ORS solutions have demonstrated advantage over glucose-based solutions in tolerance as well as reduction in frequency and duration of stool output in children and adults with cholera [25,26]. The underlying mechanism is attributed to lower osmolarity due to the polymeric structure of rice carbohydrate, nutritional benefits, and an independent yet unidentified antisecretory effect of rice [27].…”
Section: Rice-based Oral Rehydration Saltmentioning
confidence: 97%